2007
DOI: 10.4161/cc.6.12.4432
|View full text |Cite
|
Sign up to set email alerts
|

A Jekyll and Hyde Role of Cyclin E in the Genotoxic Stress Response: Switching from Cell Cycle Control to Apoptosis Regulation

Abstract: Cyclin E protein levels and associated kinase activity rise in late G 1 phase, reach a peak at the G 1 /S transition, and quickly decline during S phase. The cyclin E/Cdk2 complex has a well-established function in regulating two fundamental biological processes: cell cycle progression and DNA replication. However, cyclin E expression is deregulated in a wide range of tumors. Our recent reports have uncovered a critical role for cyclin E, independent of Cdk2, in the cell death of hematopoietic tumor cells expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…This sensitization by cAMP was dependent on cyclin E expression, thus we concluded that cyclin E induction seems to play an important role in ␥-irradiation-induced apoptosis of ASCs. The proapoptotic effect of cyclin E was apparently independent of cdk2 activity, which is in accordance with other reports (Leonce et al, 2001;Mazumder et al, 2007). Cyclin E expression has been shown to decline late in the apoptotic process, due to caspase-dependent proteolysis of cyclin E (Mazumder et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…This sensitization by cAMP was dependent on cyclin E expression, thus we concluded that cyclin E induction seems to play an important role in ␥-irradiation-induced apoptosis of ASCs. The proapoptotic effect of cyclin E was apparently independent of cdk2 activity, which is in accordance with other reports (Leonce et al, 2001;Mazumder et al, 2007). Cyclin E expression has been shown to decline late in the apoptotic process, due to caspase-dependent proteolysis of cyclin E (Mazumder et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Although we showed that anticancer drug-induced accumulation of cyclin E was clearly associated with the G 1 -S-phase transition, we could not exclude the possibility that cyclin E accumulation was also linked to apoptosis. Indeed, genotoxic stress induces both cyclin E and an associated CDK2 activity (40), and cyclin E induction is linked to apoptosis (41). However, the fact that sublethal concentrations of mitomycin C and doxorubicin also caused accumulation of cyclin E eliminated the possibility of an association between such accumulation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…189,204 Current models of the molecular network coordinating responses to DNA damage place p53 at the crossroads of several stress response pathways critical for maintaining genome integrity; including cell cycle arrest, DNA repair, mitotic catastrophe, apoptosis and cellular senescence. [205][206][207][208][209][210][211] The mechanisms by which p53 directs cells down each of these alternative avenues of cell fate determination differs among cells of various All of these pathways interact to regulate the induction of cell cycle progression and apoptosis. The Raf/MEK/ERK and PI3K/PTEN/Akt/mTOR pathways normally serve to suppress apoptosis while p53, which is induced by certain chemotherapeutic drugs and ionizing radiation, will result in increases in pro-apoptotic family members and in some cases, growth factors which may activate certain growth factor receptors.…”
Section: Roles Of Cell Cycle Proteins In Prostate Cancermentioning
confidence: 99%